Chemical Process Engineering : Design, Analysis, Simulation and Integration, and Problem Solving With Microsoft Excel-UniSim Design Software : Computation, Physical Property, Fluid Flow, Equipment and Instrument Sizing, Pumps and Compressors, Mass Transfer - Coker, A. Kayode (Scrivener ; Wiley)
Contiene: 1) Cálculos con hoja de cálculo excel, simulación de diseño UniSim; 2) Propiedad física de componentes puros y mezclas; 3) Flujo de fluído; 4) Dimensionamiento del equipo; 5) Dimensionamiento del instrumento; 6) Dimensionamiento de bombas y compresores; 7) Transferencia masiva.